Contribution of the Agricultural Teaching Approaches to Food Security: A Case of Secondary Schools in Embu County, Kenya - Njura Joseph, Hellen (University of Embu, 2020)
Continued food insecurity is a major global concern especially in Africa and Kenya in particular. The threats of the desert locust and the novel Corona Virus (Covid-19) pandemic have further accelerated this challenge. Despite her vast productive land, Kenya has been importing staple food particularly maize while her citizens have been pleading with the government to provide food especially maize flour. The youth on the other hand, cannot adequately employ the agricultural skills developed for food security despite the continued teaching of agriculture at various levels of education. The purpose of this study was to establish the contribution of the agricultural teaching approaches in secondary schools in solving the problem of food insecurity in Kenya. The study employed a descriptive survey design for objective one where qualitative data were collected and correlational research design for objectives two, three and four where both qualitative and quantitative data were obtained. A total of 198 schools in Embu County, 46,340 students, 235 agriculture teachers and 46,340 parents/guardians were targeted. The Krejcie and Morgan sample size determination procedure was employed to reach a sample size of 68 schools, 376 students, 111 agriculture teachers and 323 parents/guardians. Purposive sampling, stratified random sampling, systematic random sampling, simple random sampling as well as proportionate sampling were adopted for the county, the schools, agriculture teachers, the parents/guardians as well as the students in their focus groups respectively. Data were collected using a Students‟ Focus Group Discussion Guide, an Agriculture Teachers‟ Interview Schedule and a parents/guardians‟ questionnaire. It was then analysed using descriptive and inferential statistics. Content validity was established through expert judgment and a pilot study while Cronbach‟s alpha was calculated using SPSS version 23 to measure the reliability of the instruments. The key study findings revealed that it is the practical based agriculture teaching approaches that have major contributions to skills development for food security. Though a teaching method, digital learning was not mentioned as a standalone approach used in agriculture classes. The findings further showed that there are major constraints in the teaching and learning of secondary school agriculture that negatively impact on skills development for food security. The study concluded that agricultural teaching approaches should mainly be practical based emphasizing on the psychomotor domain. The major recommendations are that the study findings should guide the Kenyan education policymakers to develop a guideline on incorporation of agriculture practical sessions on secondary school timetables, school-community based agriculture projects and holiday-based field attachments for students for better skills development as targeted by the Competence Based Curriculum (CBC). When incorporated into the theory, the approaches can be avenues for enhanced skills development for food security emanating from the secondary school level.